2004
DOI: 10.1542/peds.113.6.e617
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in Percentiles of Growth During Early Childhood: Analysis of Longitudinal Data From the California Child Health and Development Study

Abstract: ABSTRACT. Objective. To document growth-velocity changes across major percentiles during the preschool years.Design. Analyses of longitudinal data using heightfor-age, weight-for-age, weight-for-height, and body mass index (BMI)-for-age percentiles were performed to examine crossing of major percentiles of the Centers for Disease Control and Prevention 2000 growth charts. The 5th, 10th, 25th, 50th, 75th, 90th, and 95th percentiles were defined as the major percentiles.Setting. Data from the California Child He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
1
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(99 citation statements)
references
References 18 publications
5
88
1
5
Order By: Relevance
“…O crescimento físico é reconhecido internacionalmente como indicador do estado nutricional, pois a nutrição adequada permite atingir o crescimento normal 18,19 . Assim, a avaliação antropométrica facilita a identificação e a intervenção precoces dos problemas nutricionais e de saúde emergentes, minimizando as suas conseqüên-cias 17 .…”
Section: Discussionunclassified
“…O crescimento físico é reconhecido internacionalmente como indicador do estado nutricional, pois a nutrição adequada permite atingir o crescimento normal 18,19 . Assim, a avaliação antropométrica facilita a identificação e a intervenção precoces dos problemas nutricionais e de saúde emergentes, minimizando as suas conseqüên-cias 17 .…”
Section: Discussionunclassified
“…2,3 Despite these accepted definitions, caution must be applied when diagnosing FTT on the basis of percentile shifts, because growth variants are common. 4 Actual weight Ͻ70% of predicted weightfor-length requires urgent attention. It is recognized now that earlier distinctions between organic and nonorganic FTT are overly simplistic and not clinically appropriate, 5 because many patients exhibit components of both.…”
Section: Definition Of Fttmentioning
confidence: 99%
“…21 One study found that 32% of children 0-6 months old, up to 15% of children 6-24 months old, and nearly 10% of children 24-60 months old will cross 2 major height-for-age percentiles (defined as the 5th, 10th, 25th, 50th, 75th, 90th, and 95th percentiles) during the course of normal growth. 23 Alternatively, it is possible that younger patients do not demonstrate height percentile gains after detethering surgery because a tethered spinal cord may not lead to as much growth restriction in children younger than 5 years. It is also possible that their measurements are inherently imprecise because of the inability of infants to stand, and the inability of toddlers to stand still with good posture to allow accurate measurement.…”
Section: Discussionmentioning
confidence: 99%